2019
DOI: 10.1080/15528030.2019.1651239
|View full text |Cite
|
Sign up to set email alerts
|

Exploring spirituality with older people: (1) rich experiences

Abstract: With an increasing aging population worldwide, there is a need for greater focus on the spirituality of older people, to better support them and lead them to an enhancement of their inner peace. This pilot research used a qualitative approach (with semi-structured interviews) in exploring spirituality with older people in residential aged care to understand more about the factors related to a sense of personal belief and connection that helped them in their daily lives. The research involved developing a rigor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…This witnessing capacity is speculated to help one in the reappraisal of the problem in hand, control the fluctuations of the mind and reduce the unconscious negative mental perceptions. Apart from yoga, there are some other spiritual practices such as listening to satsang [24], swadhyaya (reading Holy Scriptures) [25] and rendering seva (selfless service to the community) that have been reported to help maintain wellbeing, reduce stress, anxiety and depression [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…This witnessing capacity is speculated to help one in the reappraisal of the problem in hand, control the fluctuations of the mind and reduce the unconscious negative mental perceptions. Apart from yoga, there are some other spiritual practices such as listening to satsang [24], swadhyaya (reading Holy Scriptures) [25] and rendering seva (selfless service to the community) that have been reported to help maintain wellbeing, reduce stress, anxiety and depression [26,27].…”
Section: Introductionmentioning
confidence: 99%
“… 31 Further, in a recent study conducted in Myanmar, attending religious activities was shown to improve social relationships 32 as they enable older persons to mingle with peers, share information and enjoy their time together. In addition, religiosity helps older people to cope with their problems, 33 create inner peace 34 and thereby improve the QOL. Our finding of a positive association between attending religious activities and improved QOL warrants encouraging older people to attend religious activities regularly to improve their QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Being aware of the variety of religious and spiritual expressions can promote a better understanding of their older members, since spiritual care must be faced in a Exploring Self-Compassion in Older Adults: a systematic review __________________________________________________________________________________________ 348 Contextos holistic manner. While it is usually provided by spiritual or pastoral carers, all healthcare professionals have an important role to perform regarding this type of care (Lepherd et al, 2019).…”
Section: Discussionmentioning
confidence: 99%